Fly Ash Selection and Mix Proportioning for Ambient Cured High Strength In-situ Cast Mono Component Geopolymer Concrete - Goswami, Amiya P. (International Journal of Sustainable Construction Engineering and Technology, 2021)
Potential valorisation of fly ash powders is examined for scalable production of in-situ cast structural member with ambient cured alkali-activated geopolymer concrete. The critical issue of strength variation has been investigated by correlating with the physical and chemical properties of the original fly ash affecting water demand in mix proportion. A Class-F fly ash having fineness of 680 m2/kg Blaine’s specific surface area (SSA) and a low w/b down to 0.16 showed the 28-day strength of 99 MPa. In contrast, medium sized (416-464 m2/kg) fly ash-based mono component concrete produced the strength between 40-47 MPa and that of the coarse (157-326 m2/kg) grade < 20 MPa in the 28-day test. Lower strength was observed in Class-C fly ash containing high proportion of quartz sand exhibiting higher water demand. Results of mix proportioning suggest a higher strength gain with 20-30% increase in fly ash over the minimum cement content specified in the mix design guidelines of IS 456 : 2000 while replacing 15-20% of coarse aggregates by fine aggregates. Unconfined flexural load applied on the three M40 reinforced concrete (RC) beams, viz. mono component, bi-component geopolymer and Portland pozzolana cement showed similar deflection up to 20 kN load.